Outcome of probe-based confocal laser endomicroscopy (pCLE) during endoscopic retrograde cholangiopancreatography: A single-center prospective study in 45 patients. Issue 6 (December 2015) - Löhr, Johannes-Matthias; Lönnebro, Ragnar; Stigliano, Serena; Haas, Stephan L; Swahn, Fredrik; Enochsson, Lars; Noel, Rozh; Segersvärd, Ralf; Chiaro, Marco Del; Verbeke, Caroline S; Arnelo, Urban
Background: Diagnosis of pre-malignant and malignant lesions in the bile duct and the pancreas is sometimes cumbersome. This applies in particular to intraductal papillary mucinous neoplasia (IPMN) and bile duct strictures in primary sclerosing cholangitis (PSC). Aims: To evaluate in a prospective cohort study the sensitivity and specificity of probe-based confocal laser microscopy (pCLE) during endoscopic retrograde cholangiopancreatography (ERCP). Methods: We performed pCLE together with mother-baby endoscopy (SpyGlass) during 50 ERCP sessions in 45 patients. The Miami and Paris criteria were applied. Clinical diagnosis via imaging was compared to pCLE and the final pathological diagnosis from surgically-resected, biopsy, or cytology specimens. Patients were followed up for at least 1 year. Results: We were able to perform pCLE in all patients. Prior to endoscopy, the diagnosis was benign in 23 patients and undetermined (suspicious) in 16 patients, while six patients had an unequivocal diagnosis of malignancy. Sensitivity was 91% and specificity 52%. The positive (PPV) and negative predictive value (NPV) was 82% and 100%, respectively. Apart from mild post-ERCP pancreatitis in two patients, no complications occurred. Conclusions: Our study showed that pCLE is a safe, expert endoscopic method with high technical feasibility, high sensitivity and high NPV. It provided diagnostic information that can be helpful for decisions on patient management, especially in the case of IPMN and unclear pancreatic lesions, in individuals whom are at increased risk for pancreatic cancer.